Preparation of graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterials and method for electrochemically screening electron-rich aromatic pollutants

CN122035832BActive Publication Date: 2026-10-27NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610169340.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-05
Publication Date
2026-10-27
Estimated Expiration
2046-02-05

AI Technical Summary

Technical Problem

[0007]本发明的目的是针对富电子芳香污染物总污染负荷快速筛查方法的缺失,提供一种生物质基石墨氮-吡啶氮共掺杂二维碳纳米电极材料的制备技术及其在快速筛查富电子芳香污染物中的应用方法

Benefits of technology

1.过渡金属盐作为过渡金属软模版的引入显著改善了碳材料的电化学界面性质。软模版(如Fe、Co、Ni等)与氮原子形成M–Nx–C(M=Fe、Co、Ni)配位结构,强化碳原子石墨化的同时,能够稳定吡啶氮原子,从而获得高电导率的同时增强检测电极与富电子芳香污染物的π-π*电子转移动力学,通过定量电信号识别富电子芳香污染物含量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122035832B_ABST
    Figure CN122035832B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of environmental electrochemical detection, and discloses a preparation of graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterial and a method for electrochemical screening of electron-rich aromatic pollutants. In the pyrolysis process of nitrogen-containing biomass, a transition metal salt is added as a transition metal soft template to protect and fix pyridine nitrogen, thereby improving the electrochemical interface properties of the carbon material and improving the detection sensitivity and stability of the electrode, so that the existence of electron-rich pollutants is identified and detected under a weak bias voltage by using the number of electron transfers, and the detection limit is reduced and is lower than that of high performance liquid chromatography.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental electrochemical detection technology, and in particular to the preparation of a biomass-based graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterial and its application in the electrochemical screening of electron-rich aromatic pollutants. Background Technology

[0002] Aromatic compounds are widely used in chemical, pharmaceutical, and materials fields due to their resonance stabilizing effect caused by the delocalization of π electrons. The huge market size leads to aromatic intermediates and metabolites generated during their production, use, and disposal entering natural water bodies through various environmental pathways, including industrial emissions, agricultural runoff, and domestic sewage. Among these, emerging pollutants such as antibiotics, phenolic compounds, aromatic amines, and endocrine disruptors contain both conjugated π systems and electron-donating groups (such as hydroxyl, amino, and methoxy groups), making them typical electron-rich aromatic pollutants. These substances exhibit high chemical stability and low biodegradability, allowing them to accumulate long-term in water bodies, sediments, and organisms, posing potential risks to ecosystems and human health.

[0003] The mainstream technology for detecting organic pollutants still follows a lagging model of "on-site sampling - laboratory testing - instrument analysis". The detection results heavily rely on offline analysis of large and sophisticated instruments such as chromatography-mass spectrometry. This results in inherent bottlenecks such as long detection cycles, high equipment and maintenance costs, and slow on-site response, making it difficult to meet the urgent timeliness requirements of scenarios such as rapid screening of contaminated sites and emergency environmental detection. Electrochemical detection technology, with its advantages of rapid response, ease of operation, high sensitivity, and in-situ monitoring, holds significant research value and application potential for improving water quality safety management. However, existing electrochemical detection technologies primarily rely on the redox reactions of pollutants to identify organic pollutants. When this strategy is applied to the detection of aromatic pollutants in complex aquatic environments, it suffers from problems such as significant background interference, rapid electrode wear, and high energy consumption.

[0004] Electron-rich aromatic pollutants have high highest occupied molecular orbitals (HOMOs), allowing for the directional transfer of electrons to the lowest unoccupied molecular orbitals (LUMOs) of energy-matched carbon nanomaterials via π-π* electron donor-acceptor interactions. By converting the number of π-π* electron transfers into an electrochemical signal, highly sensitive, selective, and low-energy-consumption cluster detection of electron-rich aromatic pollutants can be achieved. Compared to current electrochemical detection techniques that aim to identify single targets, this technology better meets the macro-level needs of water environment monitoring and pollution control.

[0005] Graphite nitrogen-doped structures can inject electrons into the delocalized π-electron conjugated plane of carbon materials, enhancing the π-π* interaction with electron-rich aromatic pollutants. Simultaneously, the strongly electronegative graphite nitrogen attracts the electron clouds of neighboring carbon atoms, creating a localized positively charged region. Pyridine nitrogen-doped structures, due to the presence of exposed lone pairs of electrons, can anchor to electron-donating substituents of electron-rich aromatic pollutants, promoting π-π* interactions. Furthermore, the localized negatively charged region caused by the extraction of conjugated electrons by pyridine nitrogen can construct a surface electrostatic field with graphite nitrogen, driving the directional movement of transferred electrons to form carrier pathways and preventing electron accumulation. Therefore, graphite nitrogen-pyridine nitrogen co-doping can significantly improve the sensitivity and responsivity of two-dimensional carbon nanomaterials for the electrochemical detection of electron-rich aromatic pollutants.

[0006] The preparation of nitrogen-doped carbon nanomaterials from nitrogen-containing biomass waste through pyrolysis is one of the key technologies for solid waste resource utilization. To obtain graphene-like structures with high conductivity, the biomass sintering temperature should reach at least 900℃. However, numerous experimental studies and theoretical calculations show that as the pyrolysis temperature gradually increases, especially from 700℃ to 900℃, almost all pyridine nitrogen transforms into the more thermodynamically stable graphitic nitrogen form during structural reforming, making it difficult to obtain two-dimensional carbon nanostructures co-doped with graphitic nitrogen and pyridine nitrogen. Therefore, it is necessary to develop a pyridine nitrogen protection technology for the high-temperature pyrolysis of biomass. Summary of the Invention

[0007] The purpose of this invention is to address the lack of rapid screening methods for the total pollution load of electron-rich aromatic pollutants by providing a preparation technology for biomass-based graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanoelectrode materials and their application in the rapid screening of electron-rich aromatic pollutants.

[0008] The technical solution adopted to achieve the purpose of this invention is: A biomass-based graphitic nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterial is prepared by the following steps: Step 1: Impregnate nitrogen-containing biomass in a transition metal salt solution with added pore-forming agent; Step 2: Take out the nitrogen-containing biomass impregnated with transition metal salt solution, dry it, and obtain the precursor; Step 3: The precursor obtained in Step 2 is placed in an inert atmosphere for pyrolysis at a temperature of 700~900℃ for 1~2h to obtain carbon nanomaterials. Step 4: After grinding the carbon nanomaterial, the transition metal is dissolved and removed by acid washing with hydrochloric acid (preferably by centrifugation or filtration), then rinsed with pure water until neutral, and freeze-dried to obtain biomass-based graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterial.

[0009] In the above technical solution, the nitrogen-containing biomass in step 1 is soybean residue or coffee grounds.

[0010] In the above technical solution, the transition metal salt in step 1 is one or more of iron salt, manganese salt, and cobalt salt, and the concentration of the transition metal salt solution is 0.1~3 mol / L.

[0011] In the above technical solution, the pore-forming agent in step 1 is zinc chloride, ferric chloride, cobalt chloride, manganese chloride, etc.

[0012] In the above technical solution, the immersion temperature in step 1 is 60~90℃, the immersion time is 12~24h, and the solution is stirred during immersion at a speed of 500~700rpm.

[0013] In the above technical solution, the drying temperature in step 2 is 60~100℃.

[0014] In the above technical solution, the inert atmosphere in step 3 is argon.

[0015] In the above technical solution, in step 3, during pyrolysis, the temperature is increased from room temperature to the pyrolysis temperature at a rate of 3~5℃ / min.

[0016] Another aspect of the present invention includes biomass-based graphitic nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterials obtained by the preparation method described above.

[0017] Another aspect of the present invention includes a method for applying the biomass-based graphitic nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterials in the electrochemical screening of electron-rich aromatic pollutants.

[0018] In the above technical solution, the concentration of the electron-rich aromatic pollutant is 10 ng / L to 10 mg / L.

[0019] In the above technical solution, the electron-rich aromatic pollutant is one or more of phenol, bisphenol A, carbamazepine, tetracycline, o-aminophenol, bisphenol A, o-phenanthroline, carbamazepine, methylene blue, ciprofloxacin, tetracycline, and rhodamine B.

[0020] Another aspect of the present invention includes a method for electrochemically screening electron-rich aromatic pollutants based on biomass-based graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterials, comprising the following steps: Step 1: Take the biomass-based graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterial, Nafion solution, and anhydrous ethanol, mix them, and disperse them evenly by ultrasonication to obtain a slurry. Drop the slurry onto the surface of a conductive substrate to form a uniform modified film. After drying, obtain the working electrode. Step 2: Using a three-electrode system consisting of a reference electrode, a counter electrode, and the working electrode, prepare standard solutions of target pollutants of different concentrations as electrolytes, collect electrical signals using an electrochemical workstation, and plot standard curves. Step 3: In the three-electrode system of step 2, using the sample of unknown concentration as the electrolyte, measure the electrochemical signal and substitute it into the standard curve to obtain the concentration of electron-rich aromatic pollutants in the sample.

[0021] In the above technical solution, in step 1, the mass fraction of biomass-based graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterials in the slurry is 0.2% to 0.5%; the concentration of the Nafion solution is 5%, the volume ratio of the Nafion solution to ethanol is 1:4 to 1:99, and the volume concentration of ethanol is 50% to 100%.

[0022] In the above technical solution, the method for plotting the standard curve in step 2 is as follows: a standard solution of the target pollutant is prepared by adding the target pollutant to a phosphate buffer solution. The concentration range of the target pollutant standard solution is 10 ng / L to 10 mg / L. The electrochemical signals of the target pollutant standard solutions are measured separately. The measurement methods include Tafel curve method, chronoamperometry, chronopotentialometry, or AC impedance spectroscopy. Then, a standard curve is plotted with the standard solution concentration as the abscissa and the electrochemical signal as the ordinate. The ordinate represents the number of electrons transferred calculated by the Tafel curve method, the instantaneous current measured by the chronoamperometry, the potential change measured by the chronopotentialometry, or the impedance value change fitted by AC impedance spectroscopy.

[0023] In the above technical solution, the unknown concentration sample in step 3 is a water sample taken from the actual water environment and filtered through a filter membrane with a pore size of 0.22μm to 0.45μm. The time range for obtaining the electrical signal is 30s to 1min.

[0024] Compared with the prior art, the beneficial effects of the present invention are: 1. The introduction of transition metal salts as soft templates significantly improves the electrochemical interface properties of carbon materials. Soft templates (such as Fe, Co, Ni, etc.) form M–N bonds with nitrogen atoms. x The –C (M=Fe, Co, Ni) coordination structure enhances the graphitization of carbon atoms while stabilizing pyridine nitrogen atoms, thereby achieving high electrical conductivity and enhancing the π-π* electron transfer kinetics between the detection electrode and electron-rich aromatic pollutants. The content of electron-rich aromatic pollutants can be identified through quantitative electrical signals.

[0025] 2. Compared with carbon nanomaterials prepared without metal template modification, the addition of a transition metal template protected and fixed pyridine nitrogen under high-temperature pyrolysis conditions of 900℃. Pyridine nitrogen in the material played three important roles in promoting π-π* electron transfer kinetics. First, it lowered the LUMO energy level of the carbon nanomaterial, reducing the energy difference for electron orbital transitions. Second, it reduced the adsorption energy of pollutants by generating a π-π stacking effect with electron-donating substituents of electron-rich aromatic pollutants. Third, the localized negatively charged region around pyridine nitrogen and the localized positively charged region around graphitic nitrogen formed a surface micro-electric field, accelerating the directional transfer of electrons transferred from pollutants on the surface of the carbon nanomaterial, thus improving the sensitivity and stability of the electrical signal.

[0026] 3. By modifying the surface of a screen-printed electrode with Pd-GrN, electrochemical testing of trace electron-rich aromatic pollutants in the concentration range of 0.1 nM to 1 nM was performed at open-circuit potential. This improved the detection sensitivity and stability of the electrode, enabling the identification and detection of electron-rich pollutants using electron transfer numbers under weak bias, lowering the detection limit (below that of high-performance liquid chromatography). A good linear relationship was observed between the electron transfer number and the sample concentration. The method described in this invention is simple, the conditions are mild, and the resulting electrode material exhibits stable performance, making it suitable for rapid detection and risk warning of emerging pollutants in environmental water bodies.

[0027] 4. Compared with commonly used electrochemical detection techniques such as voltammetry (CV, DPV, etc.), this method can use zero-bias or micro-bias electrochemical techniques (such as chronoamperometry, chronopotentialometry, AC impedance spectroscopy, Tafel curve method, etc.) to capture the π-π* electron transfer driven by the orbital energy level difference and output a sensing signal. This avoids the disadvantages of voltammetry detection, such as interference from electrode oxidation and electroactive coexisting substances. At the same time, it is less affected by pH value. Attached Figure Description

[0028] Figure 1 XPS image of Pd-Gr N prepared in Example 1; Figure 2 XPS plot of GrN prepared for Comparative Example 1; Figure 3 XPS image of Pd-Gr N prepared in Example 2; Figure 4 XPS image of Pd-Gr N prepared in Example 3; Figure 5 XPS image of Pd-Gr N prepared in Example 4; Figure 6 XPS plot of GrN prepared for Comparative Example 2; Figure 7XPS images of carbon materials from the pyrolysis of coffee grounds at different temperatures (700~900℃) in Example 1; Figure 8 XPS images of carbon materials from pyrolyzed coffee grounds at different temperatures (700~900℃) for Comparative Example 1; Figure 9 EIS comparison images of Pd-GrN prepared in Example 1 and GrN prepared in Comparative Example 1 before and after adsorption of tetracycline on the surface of glassy carbon electrode. Figure 10 Tafel electrochemical test results of Pd-GrN drop-coated on the surface of a glassy carbon electrode prepared in Example 1 in tetracycline solutions with concentration gradients from 0.01 mg / L to 10 mg / L. Figure 11 The linear equation fitted by Tafel electrochemical testing of Pd-Gr N prepared in Example 1 using a glassy carbon electrode in tetracycline solutions with concentration gradients from 0.01 mg / L to 10 mg / L; Figure 12 Tafel curves of electron transfer numbers for four contaminants (phenol, bisphenol A, carbamazepine, and tetracycline) were measured on the surface of glassy carbon electrode prepared in Example 1. Figure 13 Tafel curves of mixed standard samples (tetracycline, tetracycline:phenol = 1:1, tetracycline:bisphenol A = 1:1, tetracycline:carbamazepine = 1:1) prepared in Example 1 were drop-coated on the surface of a glassy carbon electrode and used to determine the four pollutants. Figure 14 The linear equation fitted by Tafel curves of Pd-GrN prepared in Example 1 using screen-printed electrodes in tetracycline solutions with concentration gradients from 0.1 nM to 1000 nM. Figure 15 The linear equation fitted by Tafel curves of Pd-Gr N prepared in Example 1 using screen-printed electrodes in tetracycline solutions with concentration gradients from 1 μM to 1000 μM. Figure 16 The correlation diagram shows the electron transfer number and total aromatic index of 50 mixed standard samples of 16 aromatic pollutants measured on the surface of a screen-printed electrode prepared by Pd-Gr N drop-coating in Example 1. Figure 17 The relationship between the total aromatic index and total organic carbon content of actual water bodies (drinking water, seawater, tap water, river water, and secondary sedimentation tank effluent) was measured by drop-coating Pd-Gr N prepared in Example 1 onto the surface of a screen-printed electrode. Detailed Implementation

[0029] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0030] Example 1 Take 9g of coffee grounds sieved through a 60-mesh sieve, impregnate them with a 3mol / L ferric chloride solution, and add 27g of zinc chloride as a pore-forming agent. Impregnate at 80℃ and 700rpm for 20h. Dry the coffee grounds impregnated with ferric chloride in a 100℃ oven to obtain a precursor. Calcinate the precursor in a tube furnace at 900℃ with a heating rate of 5℃ / min, and pyrolyze it in an argon atmosphere for 2h to obtain a fluffy modified carbon nanomaterial. The powder obtained by grinding is acid-washed three times with 1.5mol / L hydrochloric acid, rinsed with pure water until neutral, and freeze-dried to obtain the target material (Pd-GrN).

[0031] Example 2 Take 9g of coffee grounds sieved through a 60-mesh sieve, impregnate them with a 0.1mol / L manganese chloride solution, and add 27g of zinc chloride as a pore-forming agent. Impregnate in a water bath at 80℃ and 700rpm for 20h. Dry the coffee grounds impregnated with manganese chloride in an oven at 100℃ to obtain a precursor. Calcinate the precursor in a tube furnace at 900℃ with a heating rate of 5℃ / min, and pyrolyze it in an argon atmosphere for 2h to obtain a fluffy modified carbon nanomaterial. The powder obtained by grinding is acid-washed three times with 1.5mol / L hydrochloric acid, rinsed with pure water until neutral, and freeze-dried to obtain the target material (Pd-GrN).

[0032] Example 3 Take 9g of coffee grounds sieved through a 60-mesh sieve, impregnate them with a 0.1mol / L cobalt chloride hexahydrate solution, and add 27g of zinc chloride as a pore-forming agent. Impregnate in a water bath at 80℃ and 700rpm for 20h. Dry the coffee grounds impregnated with cobalt chloride hexahydrate in an oven at 100℃ to obtain a precursor. Calcinate the precursor in a tube furnace at 900℃ with a heating rate of 5℃ / min, and pyrolyze it in an argon atmosphere for 2h to obtain a fluffy modified carbon nanomaterial. The powder obtained by grinding is acid-washed three times with 1.5mol / L hydrochloric acid, rinsed with pure water until neutral, and freeze-dried to obtain the target material (Pd-GrN).

[0033] Example 4 Take 9g of soybean residue sieved through a 60-mesh sieve, impregnate it with a 3mol / L ferric chloride solution and add 27g of zinc chloride as a pore-forming agent, and impregnate at 80℃ and 700rpm for 20h; dry the soybean residue impregnated with ferric chloride in a 100℃ oven to obtain a precursor; calcine it in a tube furnace at a temperature of 900℃ and a heating rate of 5℃ / min, and pyrolyze it in an argon atmosphere for 2h to obtain a fluffy modified carbon nanomaterial. The powder obtained by grinding is acid-washed three times with 1.5mol / L hydrochloric acid, rinsed with pure water until neutral, and freeze-dried to obtain the target material (Pd-GrN).

[0034] Comparative Example 1 Take 9g of coffee grounds sieved through a 60-mesh sieve, add 27g of zinc chloride, and soak in 150mL of deionized water in a water bath at 80℃ and 700rpm for 20h. Dry the coffee grounds in an oven at 100℃ to obtain the precursor. Calcinate in a tube furnace at 900℃ with a heating rate of 5℃ / min, and pyrolyze in an argon atmosphere for 2h to obtain a fluffy, unmodified carbon nanomaterial. The powder obtained by grinding is acid-washed three times with 1.5mol / L hydrochloric acid, rinsed with pure water until neutral, and freeze-dried to obtain the target material (GrN).

[0035] Comparative Example 2 Take 9g of soybean residue sieved through a 60-mesh sieve, add 27g of zinc chloride, and soak in 150mL of deionized water in a water bath at 80℃ and 700rpm for 20h; dry the soybean residue in an oven at 100℃ to obtain the precursor; calcine in a tube furnace at 900℃ with a heating rate of 5℃ / min, and pyrolyze in an argon atmosphere for 2h to obtain loose, unmodified carbon nanomaterials. The powder obtained by grinding is acid-washed three times with 1.5mol / L hydrochloric acid, rinsed with pure water until neutral, and freeze-dried to obtain the target material (GrN).

[0036] Test Example 1 like Figure 1 As shown in the figure, the XPS image of Pd-Gr N prepared by iron mold using coffee grounds as raw material in Example 1 clearly shows the presence of pyridine nitrogen.

[0037] like Figure 2 As shown, the XPS image of the original GrN prepared from coffee grounds without the addition of a metal template in Comparative Example 1 contains only graphitic nitrogen and no pyridine nitrogen, which confirms the soft template effect of transition metal ions.

[0038] like Figure 3 As shown in the XPS image of Pd-Gr N prepared by manganese template using coffee grounds as raw material in Example 2, the presence of pyridine nitrogen can be clearly seen.

[0039] like Figure 4As shown, the XPS image of Pd-Gr N prepared by cobalt template using coffee grounds as raw material in Example 3 clearly shows the presence of pyridine nitrogen.

[0040] like Figure 5 As shown in the XPS image of Pd-Gr N prepared using soybean residue as raw material and combined with an iron mold in Example 4, the presence of pyridine nitrogen can be clearly seen.

[0041] like Figure 6 As shown, the XPS image of the original GrN prepared from soybean residue in Comparative Example 2 without the addition of a metal template contained only graphitic nitrogen and no pyridine nitrogen, which confirmed the soft template effect of transition metal ions.

[0042] By comparing the XPS spectra before and after material modification, the transition metal template effects of iron, manganese, and cobalt were verified, all of which protected the pyridine nitrogen in the material and prevented the introduction of metals.

[0043] Both coffee grounds and soybean residue can be used as nitrogen-containing biomass in this invention. Elemental analysis of raw coffee grounds and soybean residue showed that the C, N, and O contents of the two were basically the same, and the contents of each component are shown in Table 1.

[0044] Table 1. Mass fraction of main components in coffee grounds and soybean grounds Table 2 shows a comparison of the nitrogen species content of carbon nanomaterials prepared using coffee grounds as raw material at 700-900℃ under iron mold conditions.

[0045] Table 2. Nitrogen species and content in coffee grounds-based carbon nanomaterials assisted by iron molds at different pyrolysis temperatures. like Figure 7 As shown in the XPS diagram of carbon nanomaterials prepared by adding iron molds to coffee grounds as raw materials at 700~900℃, it can be clearly seen that as the annealing temperature increases, the relative content of graphitic nitrogen gradually increases, while the relative content of pyridine nitrogen gradually decreases. This indicates that at high temperatures, graphitic nitrogen gradually becomes the main nitrogen dopant species in the material, while the content of pyridine nitrogen is lost to some extent.

[0046] Table 3 shows a comparison of the nitrogen species content of carbon nanomaterials prepared at 700-900℃ using coffee grounds as raw material under iron-free mold conditions.

[0047] Table 3. Nitrogen species and content in coffee grounds-based carbon nanomaterials without iron-mold assistance at different pyrolysis temperatures. like Figure 8As shown, without the addition of an iron mold, during the process of pyrolysis temperature rising from 700℃ to 900℃, the content of pyridine nitrogen decreased from 91.52% to 0%, while the content of graphitic nitrogen increased from 8.48% to 100%, demonstrating the trend of pyridine nitrogen to graphitic nitrogen driven by thermal energy.

[0048] The graphitic nitrogen content is the main factor affecting the π electron density of materials. Without an iron template, the pyridine nitrogen content drops sharply to 0 when the graphitic nitrogen content is increased. However, with the iron template, the pyridine nitrogen content can still be maintained when the graphitic nitrogen content is increased.

[0049] Test Example 2 like Figure 9 As shown, the electrochemical impedance spectroscopy (EIS) of Pd-GrN obtained in Example 1 and GrN obtained in Comparative Example 1 before and after tetracycline adsorption on the glassy carbon electrode surface was compared. The test parameters are as follows: The initial voltage is the open-circuit potential; Frequency range: 0.1Hz~100kHz; Amplitude: 10mV The prepared Pd-Gr N was mixed with 5% Nafion solution and anhydrous ethanol at a mass ratio of 1:1:8, and after being ultrasonically homogenized, it was drop-coated onto the surface of a glassy carbon electrode to form a uniform modified film; the working electrode was obtained by drying at room temperature for 30 minutes.

[0050] A three-electrode system was used, with Ag / AgCl as the reference electrode, a platinum sheet as the counter electrode, and a Pd-GrN modified glassy carbon electrode as the working electrode; the electrolyte was tetracycline at a concentration of 0.01 mg / L to 10 mg / L, and the tests were conducted under a nitrogen atmosphere.

[0051] Open circuit potential (OCP) and Tafel curve were tested using an electrochemical workstation at room temperature.

[0052] The test parameters are as follows: OCP scan time: 200s; Tafel scan start potential: OCP test potential -0.1V; Tafel scan termination potential: OCP test potential +0.2V; Test temperature: 20~25℃; After tetracycline adsorption, the charge transfer resistance (Rct) of Pd-Gr-N decreased by 1.24 Ω. ​​However, the Rct of GrN did not change significantly after tetracycline adsorption. This confirms that tetracycline transfers electrons to Pd-Gr-N during adsorption. Furthermore, the capacitance of PdGrN increased by 20.66%, higher than the 0.13% increase of GrN, indicating that electron-rich aromatic pollutants can spontaneously transfer electrons to PdGrN.

[0053] like Figure 10 and Figure 11 As shown, by comparing the Pd-GrN prepared by the iron metal template in Example 1, which was drop-coated onto the surface of a glassy carbon electrode, with tetracycline solutions in concentration gradients from 0.01 mg / L to 10 mg / L, Tafel electrochemical tests and fitted electron transfer graphs were performed. The increase in tetracycline concentration led to a corresponding increase in the electron transfer value. Within the concentration range of 0.01 mg / L to 1 mg / L, R... 2 A good linear relationship of 0.89 was observed, covering the range of tetracycline content in surface water or wastewater treatment plant effluent. These results confirm that the Pd-Gr-N electrode material combined with Tafel curve measurement has significant practical application potential in the electrochemical qualitative screening and quantitative detection of electron-rich aromatic pollutants.

[0054] like Figure 12 As shown, the Pd-Gr N prepared by the iron template in Example 1 was drop-coated on the surface of a glassy carbon electrode and tested in Tafel electrochemical tests for four contaminants (phenol, bisphenol A, carbamazepine, and tetracycline). This test verified the universality of electrochemical detection of electron-rich aromatic contaminants based on π-π* electron transfer.

[0055] like Figure 13 As shown, the detection capability of Pd-Gr-N for mixed electron-rich aromatic pollutants was verified through a mixed standard experiment. The electron transfer values ​​of the mixed samples showed the same trend as those of the single pollutants, indicating that it can effectively screen for the presence of mixed electron-rich aromatic pollutants in complex water bodies.

[0056] Test Example 3 like Figure 14 As shown, the Pd-GrN prepared in Example 1 was coated on the surface of a screen-printed electrode as the working electrode. Tafel electrochemical tests were performed on tetracycline solutions with concentration gradients from 0.1 nM to 1000 nM. The measured number of electrons transferred increased with the logarithm of the concentration, and the linear relationship showed a good fit. R 2 The value reached 0.91; like Figure 15 As shown, the Pd-GrN prepared in Example 1 was coated on the surface of a screen-printed electrode as the working electrode. Tafel electrochemical tests were performed on tetracycline solutions with concentration gradients from 1 μM to 1000 μM. The measured electron transfer number showed an increasing relationship with concentration, and the linear relationship showed a good fit. R 2 The value reached 0.91; The application of Pd-GrN in screen-printed electrodes shortens the mass transfer path of contaminants, improves sensitivity and responsiveness compared to glassy carbon electrodes, and is more portable, highlighting its practical application value.

[0057] Test Example 4 like Figure 16 As shown, the Pd-GrN prepared in Example 1 was coated on the surface of a screen-printed electrode as the working electrode. Through a mixed-standard experiment, 51 sample solutions prepared with 16 aromatic pollutants were subjected to Tafel electrochemical testing. The measured electron transfer number and the Total Aromatic Pullition Index (TAPI) showed a logarithmic correlation within the range of 0–5. 2 The value reached 0.98; the two showed a linear correlation in the range of 5 to 600, R0 2 The value reached 0.93.

[0058] like Figure 17 As shown, the Pd-GrN prepared in Example 1 was drop-coated onto the surface of a screen-printed electrode and subjected to Tafel electrochemical tests on different actual water bodies (drinking water, seawater, tap water, river water, and secondary sedimentation tank effluent). The measured electron transfer numbers were then incorporated into... Figure 16 The total aroma index obtained by fitting the data showed a certain correlation with the total organic carbon concentration of the water sample, R. 2 The value reached 0.9446. Among them, although the TOC of the river water was lower than that of the secondary sedimentation tank effluent, the total aromatic index was the highest, which reflects the necessity of using Pd-GrN prepared by the transition metal template method to screen the level of aromatic pollution.

[0059] The above description is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. The application of a biomass-based graphitic nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterial in the electrochemical screening of electron-rich aromatic pollutants, characterized in that, The two-dimensional carbon nanomaterial is prepared by the following steps: Step 1: Impregnate nitrogen-containing biomass in a transition metal salt solution with added pore-forming agent; the nitrogen-containing biomass is soybean residue or coffee grounds; the transition metal salt is one or more of iron salt, manganese salt, and cobalt salt; the pore-forming agent is zinc chloride. Step 2: Take out the nitrogen-containing biomass impregnated with transition metal salt solution, dry it, and obtain the precursor; Step 3: The precursor obtained in Step 2 is placed in an inert atmosphere for pyrolysis at a temperature of 700~900℃ for 1~2h to obtain carbon nanomaterials. Step 4: After grinding the carbon nanomaterial, the transition metal is dissolved and removed by acid washing with hydrochloric acid, then rinsed with pure water until neutral, and freeze-dried to obtain biomass-based graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterial. The method for electrochemical screening of electron-rich aromatic contaminants includes the following steps: Step S1: Take the biomass-based graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterial, Nafion solution, and anhydrous ethanol, mix them, ultrasonically disperse them evenly, and then drop-coat them onto the surface of a conductive substrate to form a uniform modified film. After drying, the working electrode is obtained. Step S2 involves using a three-electrode system consisting of a reference electrode, a counter electrode, and the working electrode. Standard solutions of the target pollutant at different concentrations are prepared as the electrolyte. Electrochemical workstations are used to collect electrical signals, and standard curves are plotted. The measurement methods include Tafel curve method, chronoamperometry, chronopotentialometry, or AC impedance spectroscopy. Step S3: In the three-electrode system of step S2, using a sample of unknown concentration as the electrolyte, the electrochemical signal is measured and substituted into the standard curve to obtain the concentration of electron-rich aromatic pollutants in the sample.

2. The application as described in claim 1, characterized in that, In step 1, the concentration of the transition metal salt solution is 0.1~3 mol / L; the immersion temperature is 60~90℃, the immersion time is 12~24h, and the solution is stirred during immersion at a stirring speed of 500~700 rpm.

3. The application as described in claim 1, characterized in that, The drying temperature in step 2 is 60~100℃, the inert atmosphere in step 3 is argon, and during pyrolysis, the temperature is increased from room temperature to the pyrolysis temperature at a rate of 3~5℃ / min.

4. The application as described in claim 1, characterized in that, The concentration of the electron-rich aromatic pollutant is 10 ng / L to 10 mg / L; the electron-rich aromatic pollutant is one or more of phenol, o-aminophenol, bisphenol A, carbamazepine, methylene blue, ciprofloxacin, tetracycline, and rhodamine B.

5. The application as described in claim 1, characterized in that, In step S1, the mass fraction of the biomass-based graphite nitrogen-pyridine nitrogen co-doped two-dimensional carbon nanomaterial in the slurry is 0.2% to 0.5%; the concentration of the Nafion solution is 5%, and the volume ratio of the Nafion solution to ethanol is 1:4 to 1:

99.

6. The application as described in claim 1, characterized in that, The standard curve plotting method in step S2 is as follows: a standard solution of the target pollutant is prepared by adding the target pollutant to a phosphate buffer solution. The concentration range of the target pollutant standard solution is 10 ng / L to 10 mg / L. The electrochemical signal of the target pollutant standard solution is measured by Tafel curve method, chronoamperometry, chronopotentialometry, or AC impedance spectroscopy. Then, a standard curve is plotted with the standard solution concentration as the abscissa and the electrochemical signal as the ordinate. The ordinate represents the number of electrons transferred calculated by Tafel curve method, the instantaneous current measured by chronoamperometry, the potential change measured by chronopotentialometry, or the impedance change fitted by AC impedance spectroscopy.

7. The application as described in claim 1, characterized in that, The unknown concentration sample in step S3 is a water sample taken from an actual aquatic environment and filtered through a filter membrane with a pore size of 0.22μm to 0.45μm. The time range for acquiring the electrical signal is 30s to 1min.